The critical role of matrix metalloproteinase 9-mediated microglial polarization in perioperative neurocognitive disorders of aged rats - Xin, Xi; Zhang, Haonan; Yang, Chenyi; Wang, Xinyi; Zhang, Lin; Ma, Ji; Wang, Haiyun (Frontiers in Immunology, 2025)
BackgroundPerioperative neurocognitive disorders (PND) is a significant clinical syndrome and neuroinflammation is an important pathological process. Matrix metalloproteinase 9 (MMP9) as a Zn2+-dependent matrix enzyme, not only maintains the integrity of the blood-brain barrier and synaptic plasticity, but also plays a key regulatory factor in peripheral and central nervous inflammation. This study aimed to investigate the effects of MMP9-mediated microglial polarization on surgery-induced neuroinflammation in aged rats and to provide novel targets for prevention and treatment of PND.MethodsThis study utilized an intraperitoneal injection of SB-3CT, an MMP9 inhibitor, to impede the action of MMP9. Morris water maze and novel object recognition test were conducted to assess behavioral performances. Western blot was employed to examine hippocampal inflammatory factors. Immunofuorescence and flow cytometry were used to examine the transformation of microglia phenotype.ResultsThe findings demonstrated that surgical intervention induced significant impairment in learning and memory performance in aged rats, accompanied by elevated MMP9 expression, exacerbated hippocampal inflammation, and microglial polarization characterized by a predominant M1 phenotype. Administration of SB-3CT effectively reversed these pathological manifestations.ConclusionThe inhibition of MMP9 can enhance neurological function by modulating the polarization of microglia and alleviating neuroinflammation, which is a new approach for perioperative neuroprotection in high-risk PND patients.